Psychological well-being in former drug users - Ranuwijaya, Ryan; Purnomosidi, Faqih; Musslifah, Anniez Rachmawati (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
This study aims to examine the dynamics of recovery among former drug users through the lens of psychological well-being, based on the six dimensions developed by Carol D. Ryff (1989): self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth. A qualitative approach, employing a narrative case study design, was used to explore in depth the experiences of two primary informants who have been drug-free for over a year, along with two supporting informants. Data were collected through semi-structured interviews, non-participant observation, and information gathering from various relevant sources. The findings indicate that the cessation of substance use does not solely mark recovery, but also involves the formation of a new identity, psychological growth, and meaningful social engagement. External factors such as family support, social acceptance, and participation in positive activities were found to contribute to sustained recovery. These results underscore the importance of a holistic recovery approach grounded in humanistic values and contextualized within the individual’s social reality.